Representasi Pendidikan Agama Dalam Keluarga Untuk Mencegah Kenakalan Remaja - Zakaria, Zea Ahmad; Fatmawati, Fapat; Santoso, Try Riduwan (Prodi PAI IAILM Suryalaya, 2024)
This study aims to explain and analyze the representation of religious education in the family in preventing juvenile delinquency in Sukapada Village, Pagerageung District, Tasikmalaya Regency. The method used for this research is descriptive quantitative. Located in Cidahu Village, Sukapada Village, Pagerageung District, Tasikmalaya Regency. The population in this study were parents who had adolescents aged 12-18 years in Kampung Cidahu RW 014 Sukapada Village, Pagerageung District, Tasikmalaya Regency, totaling 51 people. The sampling technique was carried out in a simple way to 30 respondents. The data collection techniques using observation, questionnaires and interviews. As well as the data analysis technique used is correlation analysis with Rank Spearman. Based on the research results, it is stated that religious education in the family in Cidahu Village, Sukapada Village has a very influential correlation with the prevention of juvenile delinquency. With an r_s result of 0.66 and in the High classification, because it is in the interval 0.61-0,80. The degree of determination is 43,56%, and the remaining 56,44% is determined by other factors. For example, a teenager's genetics (heredity) (congenital traits), family education, community environment, and influence from peers, as well as other factors that can influence religious education in the family itself. As for the comparison between